Implementasi Ta'zīr dalam Memperkuat Kedisiplinan dan Tanggung Jawab Santri Putra di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun 2024/2025: Penelitian - Intan, Mas Ayu; Setyaningsih, Rina; Pujianti, Etika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe and analyze the implementation of ta‘zīr in strengthening the discipline and sense of responsibility of male students at Pondok Pesantren Hidayatul Mubtadiin, Jati Agung, South Lampung, in the 2024/2025 academic year. The issues addressed in this research include: (1) how ta‘zīr is implemented toward male students, (2) the types of violations and the corresponding forms of ta‘zīr applied, and (3) the impact of ta‘zīr on enhancing students’ discipline and responsibility. This study employs a qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews with the boarding school administrators (including the head, deputy head, secretary, security personnel, education division, and room supervisors), as well as documentation. The research subjects consist of administrators and male students who have received ta‘zīr sanctions. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The findings indicate that ta‘zīr is systematically implemented as a means of moral and disciplinary guidance. Common violations include failing to attend congregational prayers, skipping religious classes (ngaji diniyah), neglecting yasinan recitations, smoking, stealing, carrying mobile phones without permission, and fleeing from the boarding school. The types of ta‘zīr imposed are adjusted based on the severity of the violations, including being doused with dirty water, standing punishment (disetrap), having their head shaved, being assigned expiatory tasks (dikifarat), having their violations displayed publicly (dipamflet), and being barred from certain activities. The application of ta‘zīr has shown positive effects in fostering a sense of responsibility and improving students’ discipline, although challenges remain, such as lack of individual awareness and environmental influences. A reward system is also applied to balance the disciplinary approach, making student development more effective.